The impact of collaborative planning of an oral task on learners’ language performance in an EFL context - Lima Terres, Mariana (2021)
Learning a new language is permeated by several cognitive processes which are believed to demand a high load of attentional resources during oral performance (SKEHAN, 2014). Strategic (ELLIS, 2005) and collaborative planning (SWAIN, 2000) appear as an alternative to lower these demands. In the light of Task Based Language Teaching (TBLT) (COOK, 2011; EAST, 2017) and aiming at contributing to this background, in this study, an oral task was elaborated with the purpose to analyze the performance of basic speakers of English as a Foreign Language from a language course in an oral task under two different conditions: after individual and collaborative strategic planning. Fourteen students were divided into two groups: four pairs planned collaboratively, and six students planned individually. Both groups had ten minutes to plan, followed by a few minutes to record their messages. Participants also answered a perception questionnaire concerning the activity. Statistical results indicated that students performing under the peer-planning condition had higher scores in all three measures of adequacy: organization, convincingness, and clarity than students performing under the individual-planning condition, which was confirmed by the results of the independent t-test. Furthermore, qualitative results showed that most students appeared to enjoy the task, especially the ones who performed under the peer-planning condition. These contributions bring important implications for classroom, allowing teachers to acknowledge collaborative strategic planning as a valuable tool.